(untitled)
Micropropagation protocol for vegetable type Aloe vera (Aloe barbadensis Mill.) has be-en developed using shoot tip explants. The protocol standardized for multiple micro-sucker proliferation, induction of in vitro adventitious roots and acclimatization of rooted micro-sucker from in vitro environment to greenhouse condition. Maximum proliferation of micro-suckers was obtained with combined supplementation of Benzyl adenine BA) 2 mg + Thidiawran TOZ) 0.5 mg T 0.1 mg Naphthalene acetic acid (NAA) to per liter basal Murashige & Skoog (MS) medium containing 0.8% agar and 3 o/o sucrose. The maximum rootable micro-sucker(-2 m) long were achieved after transfer of culture to hormone free medium for two weeks. The elongated micro-suckers were rooted successfully under in vitro condition. The better quality adventitious roots formation observed with NAA 0.5 mg/I supplemented 10 1/, MS medium. The regenerated plants were successfully acclimatized under Hi-Tech greenhouse and maintained in protrays for further growth and deve lopment , number=2, journal=Indian Journal of Arid Horticulture, year=2025, month=Mar., pages=1–4